2017
DOI: 10.1007/s40430-017-0848-z
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior analysis of coated cutting tool using analytical solutions

Abstract: Nowadays, almost all cutting tools are coated due to improvements in manufacturing processes. The two main reasons are: (1) coatings allow a cut with less friction and less wear resulting in longer tool life and (2) thermal barrier effect, since the contact between workpiece-toolchip occurs in the coating and not in the tool material (substrate). This paper analyzes, the thermal effect of the coating without considering the tribological effect. The thermal behavior with three types of coating: cobalt (Co), tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…[4][5][6][7] Coating materials with thermal barrier properties have an important influence on the heat transfer process. 8,9 Oliveira et al 10 coated three types of coatings (Co, TiN, Al 2 O 3 ) on the substrate of K10 cemented carbide, applied a constant heat flux to the surface of the cutting tool to simulate the heat generated in the cutting interface, and studied the transient thermal behavior of coated tools with different coating thickness. By analyzing the evolution of the temperature at the cutting interface in contact with the heat flux and the evolution of the temperature at the coating-substrate interface, it is found that the coating has a thermal barrier effect, even coatings with a thickness of 2 μm can produce a temperature reduction of up to 14%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] Coating materials with thermal barrier properties have an important influence on the heat transfer process. 8,9 Oliveira et al 10 coated three types of coatings (Co, TiN, Al 2 O 3 ) on the substrate of K10 cemented carbide, applied a constant heat flux to the surface of the cutting tool to simulate the heat generated in the cutting interface, and studied the transient thermal behavior of coated tools with different coating thickness. By analyzing the evolution of the temperature at the cutting interface in contact with the heat flux and the evolution of the temperature at the coating-substrate interface, it is found that the coating has a thermal barrier effect, even coatings with a thickness of 2 μm can produce a temperature reduction of up to 14%.…”
Section: Introductionmentioning
confidence: 99%
“…Coating materials with thermal barrier properties have an important influence on the heat transfer process 8,9 . Oliveira et al 10 . coated three types of coatings (Co, TiN, Al 2 O 3 ) on the substrate of K10 cemented carbide, applied a constant heat flux to the surface of the cutting tool to simulate the heat generated in the cutting interface, and studied the transient thermal behavior of coated tools with different coating thickness.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that with the increase of coating thickness, the temperature in the tool-chip interface increased with the coating thickness, the temperature in the coated tool body decreased significantly. Oliveira [10] coated the substrate of K10 carbide tool with three different coatings (Co, TiN, Al 2 O 3 ) and loaded a constant heat flow q(t)=25×10 5 W/m 2 on the tool surface (simulating the heat flow density at the tool-chip interface under orthogonal cutting conditions). The experimental temperature on the tool surface of the coated tool is much higher than that of the uncoated tool due to the heating resistance of the coating.…”
Section: Introductionmentioning
confidence: 99%